Hubungan Iklim Pelayanan dengan Kualitas Pelayanan pada Perawat Unit Rawat Jalan RS Pemerintah X - Jupitawati, Ratna; Sulastiana, Marina; Yanuarti, Nurul (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The purpose of this study was to determine the relationship between service climate and service quality for nurses in the Outpatient Unit of Government Hospital